2022
DOI: 10.1073/pnas.2114672119
|View full text |Cite
|
Sign up to set email alerts
|

Highly motile cells are metabolically responsive to collagen density

Abstract: Altered tissue mechanics and metabolism have gained significant attention as drivers of tumorigenesis, and mechanoresponsive metabolism has been implicated in migration and metastasis. However, heterogeneity in cell populations makes it difficult to link changes in behavior with metabolism, as individual cell behaviors are not necessarily reflected in population-based measurements. As such, the impact of increased collagen deposition, a tumor-associated collagen signature, on metabolism remains ambiguous. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Our data suggest that targeting mitochondrial respiratory chain components could be one potential approach to overcome decreased drug sensitivity in highly proliferative cancer cells, enhancing success in cancer treatment, as also suggested in recent literature . In addition, it has been reported that migrating and metastasizing cells enhance their metabolic activity, and targeting mitochondria might potentially limit their mobility and metastasis . It is worth noting that the IC50 of DOX found in our 3D culture was higher than that reported for 2D cell culture (1–10 μM) .…”
Section: Resultssupporting
confidence: 79%
“…Our data suggest that targeting mitochondrial respiratory chain components could be one potential approach to overcome decreased drug sensitivity in highly proliferative cancer cells, enhancing success in cancer treatment, as also suggested in recent literature . In addition, it has been reported that migrating and metastasizing cells enhance their metabolic activity, and targeting mitochondria might potentially limit their mobility and metastasis . It is worth noting that the IC50 of DOX found in our 3D culture was higher than that reported for 2D cell culture (1–10 μM) .…”
Section: Resultssupporting
confidence: 79%
“…Mechanistic insight into these new functions may help to develop effective DDR1-based therapy in order to improve anti-tumor effects of the currently used therapy. Finally, additional exciting new findings on DDR1 tumor function may be expected in the future, such as tumor cell metabolism, another hallmark of cancer (1,2) influenced by TME collagens (45).…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Matrix architecture in uences cellular energetics [32][33][34][35] and ECM stiffness has been linked to glycolysis 34 and mitochondrial reprogramming 36 in normal epithelial cells. Also, changes in the ECM stiffness alter mitochondrial dynamics and triggers an enhanced redox response 36,37 .…”
Section: Discussionmentioning
confidence: 99%